Explaining the relationship between attachment anxiety, eating behaviour and BMI. (1st August 2018) - Wilkinson, Laura L.; Rowe, Angela C.; Robinson, Eric; Hardman, Charlotte A.
Abstract: Previous research indicates that attachment anxiety (fear of abandonment) is predictive of overeating and higher body mass index (BMI). The current study explored the nature of the mechanisms underpinning this relationship. Study 1 assessed the relative contribution of 'emotional eating', 'susceptibility to hunger' and 'uncontrolled eating'. Study 2 assessed whether misperception of emotion and poor emotion management would mediate the relationship between attachment anxiety and stress-induced eating (and then BMI). Two cross-sectional online questionnaire studies were conducted (Study 1  N  = 665, & Study 2  N  = 548), in UK and US-based samples, which assessed attachment orientation and BMI alongside the potential mediators. The relative contribution of emotional eating, susceptibility to hunger and uncontrolled eating (Study 1) and difficulties in emotion regulation and stress-induced eating (Study 2) as mediators of this relationship were examined. In Study 1, parallel multiple mediation analysis (PROCESS) showed that emotional eating and susceptibility to hunger (but not uncontrolled eating) were significant mediators of the relationship between attachment anxiety and BMI. In Study 2, serial mediation analysis showed that difficulties in 'engaging with goal directed behaviours when upset' and stress-induced eating operated in series to significantly mediate the relationship between attachment anxiety and BMI. These findings suggest that attachment anxious individuals feel less capable in disengaging from negative emotions and go on to try to soothe themselves through eating which has a negative impact on their BMI. There was less support for an explanation of the relationship between attachment anxiety and BMI based around the misperception of emotion. Taken together, the findings highlight attachment anxiety and emotion regulation strategies as key targets for interventions that aim to reduce overeating and excess body weight.